ANALISIS PENDAPATAN WARUNG TRADISIONAL DENGAN MUNCULNYA TOKO MODERN (MINIMARKET) DI KECAMATAN KUTA SELATAN, KABUPATEN BADUNG - Lenia, Ni Kadek Novisca Ayu; Arka, Sudarsana (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 12 No 3 (2023): Vol.12.3. MARET 2023[166-230]DO - 10.24843/EEP.2023.v12.i03.p03, 2023)
The presence of minimarkets is a concern for small traditional food stall owners as it can potentially decrease their income. This study analyzes the influence of working hours, distance of business, and duration of business on the income of traditional food stalls in Kuta Selatan District, Badung Regency. The research sample consists of 99 traditional food stalls. The results of the binary logistic test indicate that the existence of minimarkets can potentially decrease the income of traditional food stalls by 53.5%. Simultaneously, working hours, distance of business, and duration of business affect the income of traditional food stalls. Partially, working hours, distance of business, and duration of business have a positive and significant influence on the income of traditional food stalls. The research model explains approximately 29.80% of income probability, while 70.2% is explained by other factors. In conclusion, the presence of minimarkets has a negative impact on the income of traditional food stalls, and working hours, distance of business, and duration of business also partially affect the income. keyword : Income of traditional stalls, working hours, business distance, length of business.